Propranolol for primary and secondary prophylaxis of variceal bleeding in children with cirrhosis - Özsoylu, Şinasi; Koçak, Nurten; Demir, Hülya; Yüce, Aysel; Gürakan, Figen; Özen, Hasan (The Turkish Journal of Pediatrics, 2000)
Variceal bleeding due to portal hypertension is a frequent and severe complication of cirrhosis in children as in adults. The prophylactic approach is important for these high mortality bleedings, both for the first and for recurrent attacks. Variceal bleeding/rebleeding rates were evaluated in sixty patients with cirrhosis who received 1-2 mg/kg/day propranolol p.o. for 1-14 years. According to Child-Pugh classification, 33 patients were Class A, 22 Class B, and five Class C. Patients were divided into two groups according to whether they had variceal bleeding before starting propranolol treatment (secondary prevention; 15 patients) or not (primary prevention; 45 patients). Seven (15.6%) of 45 patients experienced bleeding on propranolol therapy in the primary prevention group, while eight (53.3%) of 15 patients bled in the secondary prevention group (p < 0.01). Propranolol was found effective in primary and secondary prevention in Class A patients, while it was effective only for primary prevention in Class B and C patients. Propranolol administration is useful for preventing first and recurrent variceal bleeding in Class A cirrhotic patients. In Class B and C cirrhotic patients, it is effective only for preventing the first bleeding episode.